Menopause and cognitive complaints: are ovarian hormones linked with subjective cognitive decline?. (4th July 2021) - Reuben, R.; Karkaby, L.; McNamee, C.; Phillips, N. A.; Einstein, G.
Abstract: Subjective cognitive decline (SCD) and the loss of ovarian hormones after menopause have been independently linked to later-life Alzheimer's disease (AD). The objective of this review was to determine whether menopause and the loss of ovarian hormones contribute to cognitive complaints and SCD in women. This would suggest that SCD at the menopausal transition might be an important marker of eventual cognitive decline and AD. We conducted a literature search using PubMed, PsycINFO and Web of Science in July 2020. All English-language studies assessing SCD and cognitive complaints with respect to menopause and ovarian hormones were included. A total of 19 studies were included. Studies found that cognitive complaints increased across the menopause transition and were associated with reductions in attention, verbal and working memory, and medial temporal lobe volume. Women taking estrogen-decreasing treatments also had increased cognitive complaints and reduced working memory and executive function. The current literature provides impetus for further research on whether menopause and the loss of ovarian hormones are associated with cognitive complaints and SCD. Clinicians may take particular note of cognitive complaints after menopause or ovarian hormone loss, as they might presage future cognitive decline.